2014
DOI: 10.2522/ptj.20130587
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fear-Avoidance Beliefs on Disability in Patients With Subacromial Shoulder Pain in Primary Care: A Secondary Analysis

Abstract: Fear-avoidance beliefs contribute significantly to baseline disability but not to disability change scores after 3-month follow-up. Duration of complaints and baseline disability were the main factors influencing disability change scores. Although the results help to improve understanding of the role of fear-avoidance beliefs, further studies are needed to fully understand the influence of psychological and clinical factors on the development of disability in patients with subacromial shoulder pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 54 publications
4
89
0
Order By: Relevance
“…The most frequently used study design was cross-sectional (n=5) 29 32 35 36 38. Other study designs were case–control (n=1),34 case series (n=1),37 RCT (n=1)31 and cohort (n=2) 30 33…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most frequently used study design was cross-sectional (n=5) 29 32 35 36 38. Other study designs were case–control (n=1),34 case series (n=1),37 RCT (n=1)31 and cohort (n=2) 30 33…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the participants was 48.8 years, ranging from 1836 to 82 years 33. Six studies included participants with LE,29–31 33–35 two studies included participants with RT,32 36 one study included participants with AT37 and one study included participants with PT 38…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In LE, some studies have reported higher levels of anxiety and depression,20 21 whereas others have not 9 10. Pain and disability of shoulder impingement are associated with pain catastrophisation and kinesiophobia 22. Investigating lower limb tendinopathies, no association between anxiety, depression and PT was found, whereas there is a negative effect of kinesiophobia on the recovery from physical work of heel rise  in AT 12 23…”
Section: Introductionmentioning
confidence: 99%